Experimental Phenomenology as an Approach to the Study of Contemplative Practices - Lundh, Lars-Gunnar (Frontiers in Psychology, 2022)
During history humans have developed a large variety of contemplative practices, in many different areas of life, and as part of many different traditions and contexts. Although some contemplative practices are very old, the research field of Contemplation Studies is young, and there are no agreed-upon definitions of central concepts such as contemplative practices and contemplative experiences. The present paper focuses on contemplative practices, defined as practices that are engaged in for the sake of the contemplative experiences they afford (e.g., the contemplation of nature, or the contemplation of various aspects of being-in-the world). The purpose of the present paper is to discuss the potential of experimental phenomenology to contribute to the development of the research field of Contemplation Studies. Experimental phenomenology is defined as the investigation of phenomenological practices and their effects on experience. Phenomenological practices involve intentional variations of experiencing by means of changes in the direction of attention and the choice of attitude, typically as guided by verbal instructions or self-instructions. It is suggested that contemplative practices represent a subcategory of phenomenological practices. Two different varieties of experimental phenomenology are described and illustrated in the present paper: (1) an informal variety which involves the development of new phenomenological practices by creative variation of procedures and observation of effects; and (2) a more rigorously scientific variety, which involves the systematic variation of phenomenological practices in accordance with experimental designs to study their experiential effects. It is suggested that the development of contemplative practices during the ages is the result of an informal experimenting of the first kind; this variety of experimental phenomenology can also be used to develop personalized health interventions in a clinical setting. As to the more rigorously scientific experimental phenomenology, it is possible that it may lead not only to an improved understanding of general principles underlying contemplative practices, but also to a more systematic development of new contemplative practices. The experimental-phenomenological approach to contemplative practices is illustrated by various examples involving mindfulness, gratitude, receiving and giving.